The impact of generic strategies on company performance: a case of the bakery industry in Zimbabwe. - Ruduvo, Phibion (Midlands State Univeristy, 2017)
The study sought to find out the impact of generic strategies on company performance; a case of the bakery industry in Zimbabwe. The researcher therefore seeks to establish whether the varying efforts made in implementing generic strategies is generating results or not and also what can be done to enhance results of the same. The following are the objectives of the research: to find out the ways in which bakeries are applying cost reduction strategies, to identify focus strategies that are being implemented by bakeries in Zimbabwe, to find out how differentiation strategies are being employed by bakeries and to bring out the benefits and drawbacks of applying generic strategies. A review of related literature was also carried out in a bid to establish what other renowned authors had to say on Porter’s generic strategies. The research was carried out on 24 bakeries headquartered around and 3 key informant interviews. 24 questionnaires were distributed out to the heads of different bakeries and six managerial interviews were contacted. Data was presented using diagrams and tables to illustrate the research findings and responses gathered. Conclusion and recommendations were then made on how best bakeries can improve their implementation of generic strategies so that performance in terms of output, recognition and profitability can be achieved in the baking sector.